2003
DOI: 10.1002/hed.10267
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland surgery: 4‐Year review of 118 cases in an Asian population

Abstract: This is the first report documenting that most benign parotid tumors are WT and not PA. MT risk is greater in those less than 50 with pain and a noninferior pole lesion. Cystic lesions such as WT require great care in the evaluation of FNA findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
4
15
0
Order By: Relevance
“…In general, is seems that CanAd may not develop in major salivary glands. Cases reported thus far in the major salivary glands (parotid, submandibular) are either not well illustrated or lack immunohistochemistry studies to confirm the diagnosis [25,64,69,[92][93][94][95]. Additional investigation is encouraged.…”
Section: Clinical Informationmentioning
confidence: 99%
“…In general, is seems that CanAd may not develop in major salivary glands. Cases reported thus far in the major salivary glands (parotid, submandibular) are either not well illustrated or lack immunohistochemistry studies to confirm the diagnosis [25,64,69,[92][93][94][95]. Additional investigation is encouraged.…”
Section: Clinical Informationmentioning
confidence: 99%
“…However, amongst LMs closely associated with the FN, some incidences of FN injury have been reported as much higher than the rate for standard parotid surgery [4][5][6][7][8][9]. This is expected because the LM can involve local soft tissue altering typical anatomy, can completely surround the FN, and can elongate the FN, thus displacing branches of the facial nerve from their typical and expected locations [1].…”
Section: Discussionmentioning
confidence: 94%
“…Rates of short-term, postparotidectomy facial paresis range from 27 to 65%, with rates of permanent paralysis being 4-7% [6][7][8][9]. Intraoperative facial nerve monitoring during parotid surgery allows for early identification of the FN, mapping of its course through the facial region, warning of unexpected stimulation during dissection, and determination of FN prognosis at conclusion of surgery.…”
Section: Introductionmentioning
confidence: 98%
“…Ansari et al also reported monomorphic adenomas in the parotid gland, but provided no differentiation between CA and basal cell adenoma [23]. In addition, six of these reports did not provide specific information, such as clinical symptoms, histologic findings, or treatment methods [5,[8][9][10][11][12][13][14][15][16][17][18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%